HUBUNGAN PUSAT-DAERAH PASCA UNDANG-UNDANG CIPTA KERJA - Suhud Alynudin; Tjahyo Rawinarno; Agus Widiarto; Haryo Setyoko; Najwa Shafira (LPPM STIA Banten, 2023)
Found of some local government leader who caught as corruptor make central government reformed the local leader election. One of the way is Omnibus Law's production. This Research using normative jurisdiction which is based on systematical law. The research method used is statute approach. The result are diversification between local government and central government already ruled by Undang-Undang Dasar 1945 as the highest Indonesia source of law, including the mechanism of local government.